The opposite of fate : a book of musings - Tan, Amy (Putnam, 2003)
Born into a family who believed in fate, Amy Tan has always looked for alternative ways to make sense of the world. And now, in The Opposite of Fate, her first book of non-fiction she shares her thoughts on how she escaped the expectations and curses of her past, and created her own destiny.